Case Report: Extensive Temporal Bone Invasion in a Giant Vestibular Schwannoma - Lyu, Fang; Gan, Jinlu; Wang, Haijun; Zhao, Hongyang; Wang, Lei; Zhang, Fangcheng (Frontiers in Surgery, 2022)
Background: Rare giant vestibular schwannomas (GVSs) invade the temporal bone extensively, which carries unique risks for surgery owing to their complicated relationship with adjacent structures, difficult dissection of the temporal bone, and high risk of complications. The underlying mechanism of this invasive behavior remains unknown. Case description: We report on a 28-year-old woman who presented with typical hearing loss and facial paralysis (House-Brackmann II). Magnetic resonance imaging exhibited a giant mass (~5.0 cm) in the right cerebellopontine angle (CPA), petrous apex, and middle cranial fossa. Her primary diagnosis was GVS with petrous apex invasion. With the aid of presurgical imaging reconstruction and intraoperative facial nerve monitoring, we adopted a sequential therapeutic strategy, which included microsurgery for the CPA lesion followed by gamma knife surgery (GKS) for the petrous mass. During follow-up, stable tumor control was achieved with functional preservation of the facial nerve and no other complications. The postoperative immunohistochemical examination demonstrated dramatic intratumoral inflammation, which suggested its potential role in bony erosion. We reviewed the literature of large vestibular schwannoma with a petrous invasion and further discussed its treatment. Conclusion: Microsurgery remains the top therapeutic strategy for GVS. However, gross total resection with functional preservation of cranial nerves is challenging to achieve once the temporal bone is involved. In this case, we applied a planned and sequential approach of microsurgery and GKS with a promising outcome, which highlighted this combinational strategy in this rare situation. In addition, pathological examination suggested that intratumoral inflammation might play a role in the bony erosion of GVS. Longer observation and more cases are needed to further investigate its molecular mechanism and treatment plan.